(untitled) (Acta Entomologica Serbica, 2018)
In the many years of research organized between 1977 and 2017, a total of 76 hoverfly species were collected in the protected Landscape of Outstanding Features “Vlasina” (southeastern Serbia) on six localities. Among the identified taxa there is a rare species, Cheilosia longula (Zetterstedt, 1838), which is protected in Serbia. Additionally, one potentially new hoverfly species is registered (Merodon aff. cinereus). The first species checklist of hoverflies for Vlasina is proposed.